Opportunities for sustainable waste management in the pharmaceutical industry - Nikolić, Branislava; Nikolić, Nadja; Milošević, Anica; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2024)
The pharmaceutical industry significantly impacts the environment through its activities, primarily by generating pharmaceutical waste. Pharmaceutical products can be released into aquatic environments at every stage of their life cycle: from production, through use, to disposal. The majority of pharmaceutical products discharged into the environment, particularly into wastewater, originates from patient excretions. This paper, after defining and classifying waste, outlines the legal regulations as well as the possibilities for sustainable management of pharmaceutical waste. The modern concept of pharmaceutical waste management aims to ensure that the pharmaceutical industry remains successful while becoming sustainable. Sustainable development and waste management are directly linked to the circular economy. Sustainable pharmaceutical waste management encompasses reduction, reuse, recycling, energy recovery, and disposal. These activities should be carried out by manufacturers, prescribers, distributors, pharmacists, and consumers. The waste management hierarchy represents a widely accepted and recommended order of priority actions, with waste prevention (reducing waste generation) being the most desirable option, followed by reuse, recycling, recovery, and finally disposal, which is the least desirable activity in waste management. Positive changes in the sustainability of the pharmaceutical industry cannot be achieved without active collaboration involving pharmaceutical companies, academia, and policymakers. The scientific community should intensively explore possibilities for sustainable pharmaceutical waste management. Harmonizing regulations across different countries is essential, and pharmacists in community pharmacies should work to raise public awareness about pharmaceutical waste.
Keywords: pharmaceutical waste; sustainability; waste management hierarchy; hazardous waste